(untitled) (Architecture Image Studies, 2025)
Forest and land fires (Karhutla) have become a critical environmental and socio-economic challenge in Indonesia, particularly in South Sumatra. These fires cause extensive damage to ecosystems, air quality, and human health, with significant economic consequences for the region. Despite various governmental efforts to prevent and manage Karhutla, including legislation and policy implementation, the recurring occurrence of fires highlights the challenges in effective policy execution, coordination among stakeholders, and local capacity. This study presents a Systematic Literature Review (SLR) on the effectiveness of fire prevention policies and the role of multi-actor coordination in South Sumatra’s fire management. The review synthesizes studies published between 2010 and 2023, assessing how government policies, private sector involvement, and community participation contribute to the success or failure of fire management efforts. The findings show that while policies exist, their implementation is hindered by institutional fragmentation, weak coordination, and insufficient law enforcement. In contrast, effective multi-actor coordination, particularly between government agencies, the private sector, and local communities, significantly reduces fire occurrence and intensity. The study concludes that collaborative governance frameworks, improved policy enforcement, and increased community involvement are critical to improving fire management strategies in South Sumatra. Furthermore, the study highlights the importance of integrating climate change adaptation strategies and technological innovations into fire management policies for long-term sustainability.